2004
DOI: 10.1177/073401680402900109
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Work-Family Conflict among Correctional Staff: An Exploratory Examination

Abstract: Work in corrections is generally seen as a stressful occupation. There has been a fair amount of research to date on the possible causes of stress among correctional staff. Nevertheless, the issue of work-family conflict has not received much attention in the correctional literature. For the present article, a survey of correctional staff at a Midwestern prison was conducted in order to determine the effects of measures for educational level, gender, work position, race, and supervisory status. Four different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 80 publications
0
61
0
Order By: Relevance
“…Exploratory analysis [53,54], utilizes computational models and simulation experiments to conduct scenario analysis and evaluate the behavior of complex systems [47,55]. Exploratory analysis has been utilized in different studies (e.g., [56,57]) for the evaluation of environmental policies. Unlike traditional simulation approaches, exploratory analysis does not aim to predict the behavior of a system and does not intend to optimize a system.…”
Section: Agent-based Modelingmentioning
confidence: 99%
“…Exploratory analysis [53,54], utilizes computational models and simulation experiments to conduct scenario analysis and evaluate the behavior of complex systems [47,55]. Exploratory analysis has been utilized in different studies (e.g., [56,57]) for the evaluation of environmental policies. Unlike traditional simulation approaches, exploratory analysis does not aim to predict the behavior of a system and does not intend to optimize a system.…”
Section: Agent-based Modelingmentioning
confidence: 99%
“…The current study builds on the limited but critical studies of work-family conflict in the correctional officer workforce Lambert et al, 2004;Lambert et al, 2006). We follow the recommendation of to focus on precursory psychosocial states of job burnout by measuring job stress and job satisfaction among correctional officers.…”
Section: Current Studymentioning
confidence: 99%
“…Lambert, Hogan, and Altheimer (2010) recommended considering tenure as a totality of time that an employee had worked in corrections in lieu of time spent working in a particular position. Finally, existing studies have found stress levels vary by both gender and age of the individual suggesting these factors should also be accounted for in analyses (Cheeseman et al, 2011;Dial et al, 2010;Griffin, 2006;Lambert et al, 2004).…”
Section: Family-work Conflictmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies allude to stress impairing correctional officers' family life, but focus on relationship conflict arising from work stress. For example, Lambert et al (2004) examined how work-on-family conflict negatively impacted the behaviors of correctional officers by asking questions such as, "I frequently argue with my spouse/ family members about my job" and "I find that my job has negatively affected my home life." Despite the connection researchers have drawn between a stressful work environment and a negative home life, no research has yet been conducted into whether a stressful work environment is related to a violent home life for correctional officers' families.…”
Section: Literature Reviewmentioning
confidence: 99%